Cote d'Ivoire : Economic Development Documents-National Development Plan, 2016-20. (IMF Staff Country Reports; Country Report, 2016)
This paper provides a detailed summary of Cote D'Ivoire's National Development Plan for 2016-20. The plan aims to develop Cote d'Ivoire into an emerging market economy with a strong industrial base and to reduce poverty. Specifically, the plan calls for greater agricultural output, promotion of the manufacturing sector, and improvement in the standard of living. Steps will include modernization and improvement of public administration, better education and social services, a healthier business climate and access to credit for small and medium-sized businesses, and major road and energy infrastructure projects.